The Local Anesthetic Activity of Lavandula angustifolia and Eugenia caryophyllata Essential Oils - Uthirapathy, Subasini (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Previous studies show that Lavandula angustifolia (lavender) and Eugenia caryophyllata (clove) essential oils can help relieve dental pain. Clove oil and lavender oil were tested as topical anesthetics in this study on rabbits, and their effects and likely mechanisms of action were analyzed. Clove oil and lavender oil were extracted by hydrodistillation using a Clevenger-setup apparatus. Topically applying lidocaine, clove oil, or lavender oil topically all significantly reduced corneal sensitivity. The sensitivity of the cornea was successfully reduced by treatments consisting of lidocaine at a concentration of 0.5%, 25 μg of clove oil, and 50 μg of lavender oil. When clove oil is applied topically to the cornea, it produces effects similar to those of a local anesthetic due to the involvement of the cholinergic system. To achieve the desired effect of producing local anesthesia in the cornea of the rabbit, lidocaine, clove oil, and lavender oil were applied topically to the animal. A noticeable local anesthetic effect was produced when sub-anesthetic doses of lidocaine were combined with sub-anesthetic doses of lavender or clove oil.